Stüben, P. E. 2018: The Cryptorhynchinae of the Western Palearctic / Die Cryptorhynchinae der Westpaläarktis (Coleoptera: Curculionidae). - Behne, Lutz (Contributions to Entomology = Beiträge zur Entomologie, 2018)
Stüben, P. E. 2018: The Cryptorhynchinae of the Western Palearctic / Die Cryptorhynchinae der Westpaläarktis (Coleoptera: Curculionidae). – Selbstverlag, Mönchengladbach: 518 pp., 3999 photographs mounted on 871 plates, 416 maps, 30 dendrograms (English and German) print & order Curculio Institute, Germany: Mönchengladbach, curculio@t-online.de.